1996
DOI: 10.1159/000227548
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Endothelial Cell Adhesion Molecule-1 (PECAM-1): A Potential Prognostic Marker Involved in Leukocyte Infiltration of Renal Cell Carcinoma

Abstract: We investigated immunohistochemically the leukocyte infiltrate [CD3, CD4, CD8, CD11a, CD11b, CD14, CD56, VLA-4 and platelet endothelial cell adhesion molecule-1 (PECAM-1)] and the endothelial expression of cell adhesion molecules (PECAM-1, VCAM-1, ICAM-1 and ICAM-2) in 23 renal cell carcinoma tumor tissues. Tumors with a moderate or high density of PECAM-1-positive endothelia showed a stronger infiltration with PECAM-1-positive leukocytes as compared to tumors with a low density of positive endothelia (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…A similar association was reported in patients with non-small-cell lung carcinoma 31 and in those with renal tumors. 32 These findings are not surprising. A number of recent studies have demonstrated that the inflammatory cell infiltrate significantly contributes to the angiogenic process in malignant disease.…”
Section: Discussionmentioning
confidence: 92%
“…A similar association was reported in patients with non-small-cell lung carcinoma 31 and in those with renal tumors. 32 These findings are not surprising. A number of recent studies have demonstrated that the inflammatory cell infiltrate significantly contributes to the angiogenic process in malignant disease.…”
Section: Discussionmentioning
confidence: 92%
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 99%
“…With use of the mean value, 24 (400/o) cases were positive and 36 (60%) were negative for TPnuc reactivity. The percentage of tumor cells with TPcyt ranged from 0 to 90% (mean 12 %).…”
Section: Expression Of Thymidine Phosphorylasementioning
confidence: 99%